SCIENTIFIC ATTITUDE AND THEIR RELATIONSHIP WITH STUDENTS' SCIENCE LITERACY IN JUNIOR HIGH SCHOOL - Arsyad, Arsyad; Safitriani, Safitriani (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
ABSTRACT Current education emphasizes the development of scientific attitudes such as curiosity, objectivity, and critical thinking as provisions for facing global challenges. These scientific attitudes play an important role in improving the scientific literacy of junior high school students because they encourage an understanding of science as a process of thinking and evidence-based investigation. This study aims to provide an overview of the profile of the scientific attitude ability and scientific literacy ability of students in Junior High School. The approach used in this research is quantitative with the sampling technique being total sampling. Based on the data that has been obtained, followed by the discussion described above, at the end of the study it can be concluded that the profile of the scientific attitude ability and scientific literacy ability of students in Junior High School, is dominated by students (students) with the ability of scientific attitudes with the category